2006
DOI: 10.1523/jneurosci.4142-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal CA3 NMDA Receptors Are Crucial for Adaptive Timing of Trace Eyeblink Conditioned Response

Abstract: Classical conditioning of the eyeblink reflex is a simple form of associative learning for motor responses. To examine the involvement of hippocampal CA3 NMDA receptors (NRs) in nonspatial associative memory, mice lacking an NR1 subunit selectively in adult CA3 pyramidal cells [CA3-NR1 knock-out (KO) mice] were subjected to eyeblink conditioning paradigms. Mice received paired presentations of an auditory conditioned stimulus (CS) and a periorbital shock unconditioned stimulus (US). With repeated presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 52 publications
2
49
1
Order By: Relevance
“…Late CRs were those blinks that occurred within 250 ms of the US (late CRs on the first day, sex difference effect: F (1, 16) ϭ 7.49, P ϭ 0.01; percent late CRs in males: 8 Ϯ 2; females: 22 Ϯ 5). Because late blinks more accurately predict the onset of the US, they are considered adaptive (23,24). Minimally, the present results indicate that females learned to time the CR sooner in training than did males.…”
Section: Females Outperform Males During Training With Trace Eyeblinkmentioning
confidence: 57%
See 1 more Smart Citation
“…Late CRs were those blinks that occurred within 250 ms of the US (late CRs on the first day, sex difference effect: F (1, 16) ϭ 7.49, P ϭ 0.01; percent late CRs in males: 8 Ϯ 2; females: 22 Ϯ 5). Because late blinks more accurately predict the onset of the US, they are considered adaptive (23,24). Minimally, the present results indicate that females learned to time the CR sooner in training than did males.…”
Section: Females Outperform Males During Training With Trace Eyeblinkmentioning
confidence: 57%
“…Thus, females emitted more well-timed responses than did males, suggesting that they more readily learned to time the CR. Some studies suggest that the hippocampus is involved in the precise timing of the CR (23,34). Thus, timing of the CR may inf luence the effect of learning on cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the hippocampus plays a major role in various spatial learning and memory tasks (Eichenbaum et al, 1999;Sharp, 1999;Frank et al, 2000;Brun et al, 2002Brun et al, , 2008b, in which an intact hippocampus is critical (Morris et al, 1982;Moser et al, 1993Moser et al, , 1995. Yet, the hippocampus is also involved in a number of nonspatial tasks, including declarative memory, which need not include a spatial component (Eichenbaum et al, 1999;Sharp, 1999;Kishimoto et al, 2006;Broadbent et al, 2004;Parsons and Otto, in press) (but see (O'Keefe, 1999) for an opposing viewpoint). Consistent with the observed involvement of the hippocampus in nonspatial tasks, hippocampal place cells also possess more complex properties than simply representing space in an abstract (i.e., divorced from the particulars of specific locations) sense.…”
Section: Position Coding By Grid Cellsmentioning
confidence: 99%
“…Trace eyeblink conditioning appears to require the same brainstem-cerebellar circuit for acquisition and retention as delay eyeblink conditioning (Takehara, Kawahara, & Kirino, 2003;Woodruff-Pak, Lavond, & Thompson, 1985) but, when the stimulus-free trace period is long enough (250-ms for rodents; Tseng, Guan, Disterhoft, & Weiss, 2004;Weiss, Bouwmeester, Power, & Disterhoft 1999; 500-ms for rabbits, Moyer, Deyo, & Disterhoft, 1990) the hippocampus is required as well. Lesion studies have indicated that the hippocampal formation is necessary for normal acquisition and/ or proper timing of trace eyeblink CRs (Beylin et al 2001;Ivkovich & Stanton, 2001;James, Hardiman, & Yeo, 1987;Kishimoto, Nakazawa, Tonegawa, Kirino, & Kano, 2006;Moyer et al, 1990;Port, Romano, Steinmetz, Mikhail, & Patterson, 1986;Solomon, Vander Schaaf, Thompson, & Weisz, 1986;Takehara et al, 2003;Tseng et al, 2004;Weiss et al, 1999) and for short-term retention (perhaps up to several weeks; Kim, Clark, & Thompson, 1995;Takehara, Kawahara, Takatsuki, & Kirino, 2002;Takehara et al, 2003) of trace eyeblink conditioning. However, recording studies of CA1 unit activity during trace eyeblink conditioning have yielded somewhat inconsistent results.…”
Section: Introductionmentioning
confidence: 99%